Analysis Of The Influence Of Digital Service Quality and Online Promotions on Customers Intention To Use Digital Wallet Application Gopay - K Pramudito, Dendy; Yani, Indri; Utami, Eva Yuniarti; Nuraini, Rini; Kushariyadi (Jurnal Sistim Informasi dan Teknologi, 2023)
The purpose of this study is to ascertain how consumer interest is impacted by service quality and promotion. Quantitative research methodologies are employed in this study. Questionnaires are a tool used in this survey-style research study. Probability sampling combined with the proportionate stratified random sample method was the sampling strategy employed in this study. There is one hundred in the research sample. Descriptive statistics are used in the data analysis technique. The study's findings indicate that promotion has a big impact on consumers' levels of interest. Customer interest is significantly influenced by the quality of the services provided. Promotion and service excellence have an impact on customer interest. The findings of descriptive statistics, which show an average score of 72.5, a minimum score of 32, a maximum score of 90, the highest percentage value of affirmative responses to questionnaire statements at 70%, and a R square value of 0.53, or 53%, for the quality variable service to consumer interest, all support this. These findings indicate that the variable of service quality has a stronger effect on affecting customer interest. This research focuses on service quality variables because there is a gap with previous research where service quality has no effect on interest. Apart from that, consumer interest variables have not been widely used, so this can differentiate previous research that refers to interest in using e-wallets.